Detection of a New Genetic Cluster of Influenza D Virus in Italian Cattle - Chiapponi, Chiara (Viruses, 2019)
Influenza D virus (IDV) has been increasingly reported all over the world. Cattle are considered the major viral reservoir. Based on the hemagglutinin-esterase (HEF) gene, three main genetic and antigenic clusters have been identified: D/OK distributed worldwide, D/660 detected only in the USA and D/Japan in Japan. Up to 2017, all the Italian IDV isolates belonged to the D/OK genetic cluster. From January 2018 to May 2019, we performed virological surveillance for IDV from respiratory outbreaks in 725 bovine farms in Northern Italy by RT-PCR. Seventy-four farms were positive for IDV. A full or partial genome sequence was obtained from 29 samples. Unexpectedly, a phylogenetic analysis of the HEF gene showed the presence of 12 strains belonging to the D/660 cluster, previously unreported in Europe. The earliest D/660 strain was collected in March 2018 from cattle imported from France. Moreover, we detected one viral strain with a reassortant genetic pattern (PB2, PB1, P42, HEF and NP segments in the D/660 cluster, whilst P3 and NS segments in the D/OK cluster). These results confirm the circulation of IDV in the Italian cattle population and highlight the need to monitor the development of the spreading of this influenza virus in order to get more information about the epidemiology and the ecology of IDV viruses.